Combination of sodium hypochlorite pretreatment and flotation towards separation of polycarbonate from waste plastic mixtures. (November 2019) - Zhong, Yiwei; Wang, Hui; Wang, Jianchao; Zhang, Yingshuang; Wang, Kangyu; Guo, Chenchao; Chen, Shuaijun; Luo, Maozhi; Du, Yichen; Wang, Ling
Highlights: The floating ratio of PC in flotation was selectively suppressed by surface pretreatment. The purity and recovery of separated PC were 99.8% and 100.0%, respectively. Surface pretreatment selectively induced changes in the surface properties of PC. Abstract: This study developed a novel method, surface pretreatment using sodium hypochlorite along with flotation, to facilitate separation of waste polycarbonate from plastic mixtures for recycling. Surface pretreatment was observed that has an obviously negative effect on the floating ratio of polycarbonate and the floating ratio of poly-methyl-methacrylate, polystyrene, and polyvinylchloride was not affected in flotation, and this difference in floating ratio can be expected to separate polycarbonate from plastic mixtures. The optimum conditions obtained included sodium hypochlorite concentration of 0.05 M, pretreatment temperature of 70.0 °C, pretreatment time of 60.0 min, frother dosage of 10.8 mg/L, and flotation time of 4.0 min. Under optimum conditions, polycarbonate was separated effectively from multiple plastic mixtures, and the purity and recovery were 99.8% and 100.0%, respectively. The major mechanism of surface pretreatment was ascertained by the aid of Fourier transform infrared, scanning electron microscope, energy dispersive spectrometer, and X-ray photoelectron spectroscopy, and the hydrophilic groups, pitting, and protuberances introduced on polycarbonate surface caused the reduced floating ratio of polycarbonate. Accordingly, this method can be expected to improve the recycling quality of waste plastics, and provides technological insights in the environmentally friendly disposal of waste plastics.